KOMPOSISI ZAT GIZI TEMPE YANG DIFORTIFIKASI ZAT BESI DAN VITAMIN A PADA TEMPE MENTAH DAN MATANG (Nutritional Composition of Soyben Tempeh Fortified with Iron and Vitamin A on Uncook and Cook Soyben Tempeh) - Rahayu Astuti; Siti Aminah; Agustin Syamsianah (Agritech, 2014)
Anemia is one of the most common nutritional problems in developing countries, including Indonesia. Food fortificationis one of the efforts to be made among the various solutions to improve nutrition, and one of alternative enables food to be fortified was soybean tempeh. The aim of this study was to analyze nutritional composition of soyben tempeh fortified with iron and vitamin A on both uncook and cook soybean tempeh. The treatment wasused in succession given iron (FeSO4) 90, 110, 130 and 150 mg/kg wet soybeans, and vitamin A each treatment 12 mg/kg wet soybeans, and control in this study was tempeh without fortification. Statistical analysis with anova, Kruskal Wallis test, independent t test and Mann Whitney test. Result showed no differences in levels of protein, fat, moisture, ash, carbohydrate, vitamin A, Cu and Zn (p>0,05) based treatment, both uncook and cooked tempeh. In uncook tempeh, increasing iron treatment was increasing iron level soyben tempeh fortified unless there was not significant. Protein and fat content decreased significant (p<0,05) after cooked(dibacem). Ash and carbohydrate content increased significant (p<0,05) after cooked (dibacem). Vitamin A, iron (Fe), copper (Cu) and zinc (Zn) content after cooked were not difference significantly.